THE EFFECT OF DEBT TO ASSET RATIO (DAR), CURRENT RATIO (CR) AND SIZE ON RETURN ON ASSET (ROA) AND EARNING PER SHARE (EPS) ON THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON IDX FOR THE 2016-2020 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
The purpose of this study was to determine and analyze the effect of Debt to Asset Ratio, Current Ratio and Firm Size on Return on Assets and Earnings Per Share. The research was conducted on companies in the consumer goods industry sector during the 2016-2020 period which were listed on the Indonesia Stock Exchange (IDX). The population in this study are all consumer goods companies listed on the IDX until 2020, totaling 61 companies, the method of determining the sample is purposive sampling technique. So that the population in this study are all consumer goods companies listed on the IDX until 2020, totaling 61 companies. Data analysis used multiple linear regression method. The results of the study explain that the Debt to Assets Ratio has a positive and insignificant effect, while the Current Ratio has a positive and significant effect and Firm Size has a negative and significant effect on Return on Assets. While the Debt to Assets Ratio and Current Ratio have a negative and insignificant effect, while Company Size and Return on Assets have a positive and significant effect on Earnings Per Share. Indirectly Debt to Assets Ratio, Current Ratio, and Firm Size have no effect on Earnings Per Share through Return on Assets.